KARAKTERISTIK AGROFORESTRI DAN PRAKTIK BUDAYA PENGELOLAANNYA DI NEGERI WATUI KECAMATAN ELPAPUTIH KABUPATEN SERAM BAGIAN BARAT INDONESIA - Juglans Howard Pietersz; Sofia Mustamu (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Agroforestry in Maluku (dusung) represents one of the cultural heritages that continues to be maintained in forest management practices on small islands. Watui, as an indigenous village located in the upstream area of the Tala River, plays an important role in maintaining the sustainability of the Wae Tala watershed on Seram Island, Maluku. The long-standing practice of dusung management has shaped a cultural landscape that serves as the social identity of the local community. This study aims to examine the structure and composition of dusung agroforestry systems and their cultural management practices in Watui Village. The methods employed included a dusung potential survey and interviews with 20 households directly involved in local agroforestry practices. The results showed that the agroforestry composition in Watui Village is dominated by commercially valuable species such as Pterocarpus indicus, Anthocephalus macrophyllus, Vitex cofassus, and Artocarpus champeden. The canopy structure is well developed and exhibits optimal ecological functions, characterized by five vertical strata. The local agroforestry system (dusung) in Watui Village is managed in the form of shifting cultivation fields, mixed gardens, and monoculture gardens, with management zoning that includes protected areas along riverbanks, utilization areas, and protected zones located on slopes greater than 45% or within water catchment areas. Furthermore, the community continues to uphold local wisdom that shapes the cultural landscape of the area.